Hormonal modulation of cholesterol: experimental evidence and possible translational impact. Issue 3 (May 2012) - Peri, Alessandro; Benvenuti, Susanna; Luciani, Paola; Deledda, Cristiana
Alzheimer's disease (AD) is still an incurable condition. There is in vitro evidence that estrogens exert neuroprotective effects; however, their role in the treatment of AD is still controversial. Approximately 10 years ago, a new gene, named seladin-1 (for selective AD indicator-1), was identified and found to be downregulated in brain regions affected by AD. Seladin-1 has neuroprotective properties, which have been associated, at least in part, with its anti-apoptotic activity. Estrogens stimulate the expression of the seladin-1 gene. Seladin-1 also has enzymatic activity (3-β-hydroxysterol Δ-24-reductase), which is involved in the synthesis of cholesterol from desmosterol. The amount of membrane cholesterol appears to play an important role in conferring protection to brain cells. This review focuses on the relationship between estrogens (and IGF-1, another hormone with neuroprotective properties), cholesterol and seladin-1.